EFEKTIVITAS PEMBERIAN REWARD DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI KELAS 1A MIS AT-TAQWA SAMBAS TAHUN PELAJARAN 2022-2023 - Ruzita; Topik; Mauizatul Hasanah (ADISAM PUBLISHER, 2026)
This research was motivated by indications that in learning activities using rewards in class 1A MIS At-Taqwa Sambas, teachers were seen implementing interesting learning methods so that students felt enthusiastic about learning, namely applying rewards during the learning process, this made class 1A students enthusiastic. and compete in learning. In class 1A there are several students who are lazy about writing and doing assignments, but with the reward these students become enthusiastic and become diligent in writing and doing the questions the teacher gives. This research has three research objectives, including the following: First, to determine the form of giving rewards in increasing student learning motivation in class 1A MIS At-Taqwa Sambas for the 2022-2023 academic year. Second, to determine the impact of giving rewards on students' learning motivation in class 1A MIS At-Taqwa Sambas for the 2022-2023 academic year. Third, to determine the supporting and inhibiting factors for giving rewards in increasing student learning motivation in class 1A MIS At-Taqwa Sambas for the 2022-2023 academic year. This research uses a qualitative approach while this type of research is field research. There are three types of data collection techniques in this research, namely: Interview, Observation and Documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data display, drawing conclusions and verification. Then the data validity checking techniques used are triangulation (source triangulation) and member check. The research results are: First, the form of giving rewards to increase students' learning motivation in class 1A is by giving attention and praise, giving respect and appreciation, and giving simple gifts to students. Second, the impact of giving rewards on students' learning motivation in class 1A has had a good impact, namely increasing students' attention when studying, facilitating learning activities in class, generating and maintaining students' learning motivation, controlling and changing disruptive behavior towards learning behavior and can direct good thinking. Third, the supporting factors for giving rewards in increasing students' learning motivation in class 1A are the teacher's authority to manage rewards in class, support and cooperation from the school and also the student's guardians. while the inhibiting factors are the personal costs incurred by teachers to purchase rewards in the form of prizes, a bad environment and different levels of student ability.